Human misconnection? A response to Beuthin and Bruce on medical assistance in dying providers' lived experience - Lyon, Christopher (Death studies, 2025)
Beuthin and Bruce's study 'MAiD as human connection: Stories and metaphors of physician providers existential lived experience' in this journal describes the affective experiences of Canadian Medical Assistance in Dying (MAiD) providers. A critical response to this work shows it is based on flawed premises and interpretations of its data, which centers on praising its participants in lethal injection for their very positive emotions. Their study also seems to unproblematically construct people dying by MAiD as "the other," a term that usually describes members of groups subject to individual and systemic oppression. Contextualized, their paper can be read to show how some MAiD providers may affectively and financially benefit from providing death to, and at the expense of, their suffering patients and grieving and possibly traumatized family members and witnesses. Beuthin and Bruce's study sheds new light on the provider side of MAiD and assists the case for vetting and setting suitability criteria for MAID clinicians.